A 3D FEM/BEM code for ground–structure interaction: Implementation strategy including the multi-traction problem. (October 2015) - Jean, Philippe
Abstract: The purpose of this paper is to describe the development of a 3D BEM–FEM code for ground–structure interaction. The technical choices and difficulties are reported. In particular, the multitraction problem has been implemented in 3D following a technique recently published in 2D for elastodynamics. It is showed that the separation of tractions is mandatory at corners but not at edges. The free surface and infinite interlayers are meshed by means of finite planes of varying dimensions. The paper also focuses on the validity of 2.5 approaches suggesting that in many situations the 2.5D model is well adapted. Reference situations are used for validation. The case of a pile joining a free surface and an interlayer between two different soils is described in detail. Finally computations are validated against measurements.